IMPLEMENTASI PENGUATAN PENDIDIKAN KARAKTER PADA MATERI RUANG LINGKUP BIOLOGI - SIREGAR, TIURLINA; WALUYO, JOKO; SUBIYANTO, SUBIYANTO (Jurnal Ilmu Pendidikan Indonesia, 2020)
The purpose of this study was to determine the implementation of strengthening character education to increase learning outcomes in the material in the scope of biology. The method in this research is the furpossive sampling method and the data collection technique that be used is a questionnaire, which is a data collection technique that is done by giving a set of questions or written statements to the respondent. There is an effect of the implementation of strengthening character education on the learning outcomes of biology subject in class XI SMA Negeri 4 Jayapura City. This is based on the results of the simple regression test, it is obtained that t count is greater than t table (2.174> 1.960) and the significance is 0.031 <0.05 with the regression equation Y = 63.870 + 0.177 X2 with a contribution or relative contribution of 1.7%, Increased mastery of the concept of space material the scope of biology is above 0.7, which means that students have mastery of concepts. The results of the calculation of the pretest and posttest values have an increase of 0.85 in the moderate category